Agriculture-based development: a SAM perspective on central Viet Nam - Bautista, Romeo M. (International Food Policy Research Institute, 2000)
As in most low-income countries, the majority of the poor population in Viet Nam is found in rural areas, where agriculture provides the primary means of livelihood. It has been argued that an agriculture-based development (ABD) strategy is more appropriate for Viet Nam at the present time than both import-substitution and export-led industrialization, considering its effectiveness in generating income opportunities, directly and indirectly, for the rural population. Under the ABD strategy, increased public resources allocated to agriculture and the rural sector would lead to rising agricultural productivity and rural income that in turn would create a strong demand for increased nonagricultural production in the local economy, especially of labor-intensive industrial goods and services. It is in effect a decentralized, employment-generating industrialization strategy that can lead to favorable outcomes in overall income growth and distribution. The Central Region in Viet Nam is the least developed among the three macro-regions, the rapid economic expansion during the 1990s having been concentrated in the southern and northern areas. Because Central Viet Nam is even more heavily agricultural than the rest of the country, the argument for adopting an ABD strategy would seem to apply with greater force. In this paper we make use of SAM (social accounting matrix)multiplier analysis in examining quantitatively the comparative economy-wide repercussions of exogenous income increases in agriculture (such as that arising from productivity growth) in Central Viet Nam, paying particular attention to the effects on overall income growth and equity. The equity impact is evaluated in terms of the induced relative changes on the incomes of four households groups distinguished in the study. Some policy implications of the results are discussed, emphasizing the role of macroeconomic policies in helping promote equitable growth in Central Viet Nam.